Krishna's Diabic Care: An Evidence-Based Review of Ingredients for Diabetes Control (International Journal of Ayurveda and Pharma Research, 2025)
Krishna’s Diabic Care is an Ayurvedic formulation aimed at managing diabetes by combining traditional herbal remedies with holistic approaches. This review explores the potential benefits, safety profile, challenges, and future directions of this product in the context of diabetes management. Krishna’s Diabic Care utilizes a blend of herbs traditionally used in Ayurvedic medicine, such as Trigonella foenum-graecum, Syzygium cumini, Momordica charantia, Gymnema sylvestre, Azadirachta indica, Aegle marmelos, Ocimum sanctum, Pterocarpus marsupium, Phyllanthus emblica, Tinospora cordifolia, and Picrorhiza kurroa, known for their roles in supporting blood sugar regulation, improving insulin sensitivity, and reducing complications related to diabetes. However, scientific validation through clinical trials is needed to confirm the long-term efficacy and safety of Krishna’s Diabic Care. While the product demonstrates promise, its integration into mainstream diabetes management is hindered by the lack of robust clinical evidence, potential variations in formulation quality, and regulatory challenges. Collaborations between Ayurvedic practitioners and modern researchers could further bridge traditional knowledge with contemporary medical practices, facilitating broader acceptance of Ayurveda in managing chronic conditions like diabetes. The review concludes that Krishna’s Diabic Care holds potential as part of a holistic diabetes management strategy, with the need for rigorous clinical validation to enhance its credibility and integration into global healthcare systems.